Pharmacological Characterization of a Novel Neuroactive Steroid Prodrug, NTS-104, and Its Neuroprotective Activity in Experimental Stroke Models. Issue 11 (28th September 2022) - Zhang, Li; Schwartz-Byrne, Robin; Gertz, Steven; McGuire, Matthew; Woodhouse, Colleen; Powell, Brianna; Wei, Min; Li, Chao; Billing, Clare B.; Verdoorn, Todd A.; Lam, Leslie; Parry, Tom J.; et al.
Abstract : Background: Ischemic stroke affects about 700 000 patients per year in the United States, and to date, there are no effective pharmacological agents that promote recovery. Here, we studied the pharmacokinetics, pharmacodynamics, and efficacy of NTS-105, a novel neuroactive steroid, and NTS-104, a prodrug of NTS-105, in 2 models of ischemic stroke. Methods: The pharmacodynamics and pharmacokinetics of NTS-104/105 were investigated in naive and stroke rats, and models of embolic and transient middle cerebral artery occlusion were used to investigate the dose-related effects of NTS-104. All rats were randomly assigned into the experimental groups, and all outcome measurements were performed blindly. Results: Blood plasma and brain pharmacokinetic analysis revealed that NTS-104 rapidly converted to NTS-105, which reached peak concentration at ≈1 hour after dosing and distributed similarly to normal and ischemic brains. NTS-104 administration 4 hours after embolic middle cerebral artery occlusion led to a dose-dependent improvement of neurological outcomes and a dose-dependent reduction of infarct volumes relative to vehicle-treated animals. A single dose level study confirmed that NTS-104 administered 4 hours after transient middle cerebral artery occlusion was also neuroprotective. Quantitative ELISA revealed that NTS-104 treatment resulted in time- and dose-dependent changes in AKT activation and cytokine levels within the ischemic brain, which included reductions of IL-6, VEGF, ICAM-1, IL-1β, MCP-1, RAGE, and GM-CSF. Time- and dose-dependent reductions in IL-6 and GM-CSF were also observed in the plasma along with an elevation of galectin-1. Conclusions: NTS-104 is a novel prodrug that converts to a novel neuroactive steroid, NTS-105, which improves functional outcomes in experimental ischemic stroke models.